2017
DOI: 10.1371/journal.ppat.1006741
|View full text |Cite
|
Sign up to set email alerts
|

The pUL37 tegument protein guides alpha-herpesvirus retrograde axonal transport to promote neuroinvasion

Abstract: A hallmark property of the neurotropic alpha-herpesvirinae is the dissemination of infection to sensory and autonomic ganglia of the peripheral nervous system following an initial exposure at mucosal surfaces. The peripheral ganglia serve as the latent virus reservoir and the source of recurrent infections such as cold sores (herpes simplex virus type I) and shingles (varicella zoster virus). However, the means by which these viruses routinely invade the nervous system is not fully understood. We report that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 102 publications
3
96
0
Order By: Relevance
“…Previous studies on the inner tegument proteins VP1/2 (pUL36) and pUL37 revealed that both proteins are critical for alphaherpesvirus retrograde axonal transport and neuroinvasion (6,65,66). Our findings in this study provide evidence that pUL21, as an inner tegument protein like VP1/2 and pUL37, also has a potential role in PRV retrograde axonal transport and neuroinvasion.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies on the inner tegument proteins VP1/2 (pUL36) and pUL37 revealed that both proteins are critical for alphaherpesvirus retrograde axonal transport and neuroinvasion (6,65,66). Our findings in this study provide evidence that pUL21, as an inner tegument protein like VP1/2 and pUL37, also has a potential role in PRV retrograde axonal transport and neuroinvasion.…”
Section: Discussionsupporting
confidence: 67%
“…The pUL36 large tegument protein promotes transmission from epithelial tissues to nerve endings and subsequently tethers capsids delivered into the cytosol of axon terminals to the dynein/dynactin microtubule motor complex to drive retrograde axonal transport to sensory ganglia (12, 18). The pUL37 tegument protein sustains dynein-based microtubule transport by restraining opposing plus-end motion (22). Consistent with these roles, pUL36 and pUL37 remain attached to capsids upon entry into cells (2, 3, 5, 26), with pUL36 bound directly to the capsid surface (7, 9, 27, 28) and pUL37 bound to pUL36 (10, 11, 29) such that pUL36 tethers pUL37 to the capsid (13).…”
Section: Discussionmentioning
confidence: 99%
“…Of these enzymes, only the pUL36 deubiquitinase is reported to contribute to the neuroinvasive property of these viruses (18, 19). Nevertheless, pUL37 is a critical component of the neuroinvasive apparatus (20), with an amino-terminal region essential for the delivery of incoming capsids to the neural soma by sustaining dynein-based microtubule transport in axons (21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of data from studies of HSV pathogenesis, this conclusion is reasonable. The only uncertainty is whether viral latency, which depends on the process of viral entry into neurons from epithelial tissue, might lose control of the activated innate immune response during viral infection or still retain control because of the strong neurotropic characteristic of HSV . Although there are many examples of neurotropic viruses that have the characteristics of intense neurotropism and a shorter proliferative cycle than HSV, a lower rate of neuron infection was observed for these viruses than for HSV .…”
Section: The Strategy By Which Hsv Evades Monitoring By the Immune Symentioning
confidence: 99%